Stochastic Models Quality of Electronics Systems - Eidukas, D. (Elektronika ir Elektrotechnika, 2008)
Method is offered for synthesis of stochastic distributions of defectivity levels of multiparametric ES with interindependent parameters. This synthesis can be performed in groups of parameters or for entire product according to known distributions of defectivity levels of separate parameters. For practical applications it is advisable to differentiate average defectivity levels of separate parameters according to selected defectivity level of entire product, when ratio between defectivity levels in separate groups is selected or according to needed dispersion of parameters (selected variation coefficient). Ill. 1, bibl. 6 (In English; summaries in English, Russian and Lithuanian).